Introducing an African Language for Teaching and Learning at Wits University (Nordic Journal of African Studies, 2003)
This paper discusses research relating to the attitudes of selected groups of staff and students at the University of the Witwatersrand to the introduction of an African language alongside English for teaching and learning purposes. Academic staff, academic practitioners, first year and third year students were interviewed in order to elicit their views. A distinguishing feature of the findings was the ambivalence expressed by many of the respondents to the issues investigated. Such ambivalence suggests conflicting attitudes towards, on the one hand, the importance of gaining access to English and on the other hand, the students' need to express their own identities and show solidarity with peers and community.